Rethinking the economics of rural water in Africa. (6th January 2020) - Hope, Rob; Thomson, Patrick; Koehler, Johanna; Foster, Tim
Abstract: Rural Africa lags behind global progress to provide safe drinking water to everyone. Decades of effort and billions of dollars of investment have yielded modest gains, with high but avoidable health and economic costs borne by over 300m people lacking basic water access. We explore why rural water is different for communities, schools, and healthcare facilities across characteristics of scale, institutions, demand, and finance. The findings conclude with policy recommendations to (i) network rural services at scale, (ii) unlock rural payments by creating value, and (iii) design and test performance-based funding models at national and regional scales, with an ambition to eliminate the need for future, sustainable development goals.